Roots of the Revival : American and British Folk Music in the 1950s - Cohen, Ronald D., 1940- (Book collections on Project MUSE., 2014)
In 'Roots of the Revival', Ronald D. Cohen and Rachel Clare Donaldson present a transatlantic history of folk's midcentury resurgence that juxtaposes the related but distinct revivals that took place in the United States and Great Britain.